Between Gatekeeper and Gateway : Taking Advantage of Regional and Global Value Chains by Addressing Barriers to South Africa’s Trade Competitiveness - Draper, Peter; Engel, Jakob; Krogman, Heinrich; Ngarachu, Anna; Wentworth, Lesley (World Bank, Washington, DC, 2018)
South Africa's weak post-apartheid trade performance has been a significant factor in its inability to create more jobs and achieve higher growth and productivity. Exports and inbound foreign direct investment as a share of gross domestic product have lagged other middle-income countries and both have declined in absolute terms in the past five years. South Africa is losing market share in many of its core export products, both because it is being outcompeted by more dynamic economies in East Asia and owing to its own supply-side and institutional constraints. This loss of global competitiveness in manufacturing has meant that more South African firms have turned to the domestic economy and to less demanding export markets in the rest of sub-Saharan Africa. While South Africa can continue growing through a primarily regionally focused strategy, these markets are small, and defaulting to the lower levels of productivity required to compete in the rest of Africa could undermine South Africa's competitiveness in the long term. This paper provides an overview of South Africa’s recent trade outcomes, as well as its trade policy framework, and assesses the causes of its disappointing performance. In turn, it suggests changes to trade-related policies as well as the governance and management of these policies. The paper focuses in depth on three specific trade-related constraints: transport costs, the institutional governance of trade tariffs and export promotion, and overall economic policy uncertainty. The paper proceeds to argue that the South African government would benefit from aligning its trade strategy, commercial and economic diplomacy and industrial policy with the dual objective of providing both the engine for a "Factory Southern Africa" that encompasses the rest of the SADC region, and of being the region's gateway to the rest of the world. Since South African firms will not be able to drive this approach on their own, this necessarily means forging policies and institutions that encourage investments into South Africa and the SADC region, and working with neighbors to maximize the development of regional value chains that result from such investments.